Preventing or attenuating amphotericin B nephrotoxicity with dopamine receptor agonists: a literature review - Iman Karimzadeh; Hossein Khalili; Mohammad Mahdi Sagheb (Shiraz University of Medical Sciences, 2015)
Nephrotoxicity is generally considered as the most clinically significant and dose-limiting adverse reaction of amphotericin B. Currently, only the clinical effectiveness of salt loading and administering lipid formulations of amphotericin B have been clearly demonstrated to prevent its nephrotoxicity. In this review, we collected the published data related to dopamine receptor agonists in preventing amphotericin B nephrotoxicity. A literature search was conducted by the relevant keywords like ''amphotericin B", "nephrotoxicity'', and ''dopamine'' in databases such as Scopus, Medline, Embase and ISI Web of Knowledge. Four relevant articles were considered. Results of all the 3 experimental studies demonstrated that co-administration of dopamine (0.5-10 μg/kg/min) as continuous intravenous infusion, SK&F R-105058 (10 mg/kg twice daily), a prodrug of fenoldopam, orally, or fenoldopam, a relatively selective dopamine receptor type 1 agonist, (0.5 or 1 μg/kg/min) as continuous intravenous infusion can at least significantly mitigate the decrease in creatinine clearance caused by amphotericin B. Furthermore, fenoldopam and SK&F R-105058 can also protect against or delay amphotericin B-induced tubular damages. In contrast, the only clinical trial published until now found that simultaneous continuous intravenous infusion of low dose dopamine (3 μg/kg/min) had no beneficial effects on the incidence, severity, as well as time onset of developing amphotericin B-induced nephrotoxicity in autologous bone marrow transplant and leukemia patients. Considering the lack of beneficial effects in different settings such as acute kidney injury of any cause, negative results of the only clinical trial, and risk of significant adverse reactions, continuous intravenous infusion of low dose dopamine (1-3 μg/kg/min) or selective dopamine receptor type 1 agonists (e.g., fenoldopam) currently appears to have no real clinical role in preventing or attenuating amphotericin B nephrotoxicity.